Comparing Nearshore Wave Parameters in Amurang Bay location using MIKE-21 Spectral Wave Model - Tommy Jansen (Journal of Sustainable Engineering: Proceedings Series, 2019)
Wave parameters as an accurate prediction in ocean environment are important thing for good coastal development. Spectral wind wave model as a tools in MIKE 21 SW based on unstructured mesh is used in this study which the model simulates the growth, decay and transformation of wind generated waves and swell in offshore and coastal areas. The Amurang Bay as the province of North Sulawesi Indonesia was selected as the study area which the geography position around 1012’16.16” N-124027’04.33” E to 1015’43.80” N-124032’01.06”E. The bathymetry and tide data used in this research from Indonesian Coastline Environmental map of year 1995 with scale 1:50.000 from BIG (Badan Informasi Geospasial) with a satellite data from Google earth of year 2018 and LANTAMAL Manado, the wind and current data was obtained from BMKG Manado. Time simulations are taken from 25 November to 23 December 2016 as a wet season and 25 Mei to 23 June 2016 as a dry season.The model computed the wave parameters using the forecast wind input. The synoptic map of significant wave height (Hs), wave period, wave direction are obtained from the result of simulation. During the dry and wet season conditions the predicted wave parameters as the result of the simulation with tide and wind show to be higher than with tide and no wind simulation. The average condition of significant wave height is higher in outside of bay than inside of bay.